Meningkatkan Pengetahuan Pengolahan Sampah Plastik Bagi Karyawan dan Nasabah Bank Sampah Sekumpul Martapura, Kalimantan Selatan - Anang Kadarsah; Sunardi Sunardi (Universitas Lambung Mangkurat, 2023)
Knowledge about plastic waste processing and the climate village program is very important for all people, including environmental activists and practitioners. Webinars are the most sensible choice in the era of the Covid-19 pandemic in terms of sustainable development goals. The purpose of this activity is to increase the knowledge of employees and customers of the Sekumpul Martapura Waste Bank through webinars related to plastic waste processing, and the climate village program. Activities are carried out through online seminars (webinar) using the Zoom application at the address https://lambungmangkurat.zoom.us/j/9966097636. After completing the activity, an evaluation was carried out by filling out the response form by the participants. The results of the activity show that, thank God, all the webinars can be held well and smoothly. The three webinars held included: 1) a webinar socializing the activities of the Mandatory Serving Lecturer Program (PDWA) on May 14, 2022, 2) a webinar socializing plastic waste processing at the Sekumpul Waste Bank on May 21, 2022, and 3) a webinar socializing the climate village program on on June 4, 2022. Three speakers who filled out the material for the webinar were: 1) Mr. Anang Kadarsah, S.Si.M.Si from FMIPA Lambung Mangkurat University, 2) Mrs. Dewi Heldayanti, S.Sos from the Waste Bank Sekumpul Martapura and 3) Mrs. Yunida from the Head of the DPRKPLH Banjar Regency. It was recorded that the participation of participants in participating in all activities reached an average of 85%. The output generated from this activity is a document of knowledge of managers and customers at the Sekumpul Martapura Waste Bank related to plastic waste management and food security in the climate village program.